Helminth therapy or elimination: epidemiological, immunological, and clinical considerations - Wammes, Linda J; Mpairwe, Harriet; Elliott, Alison M; Yazdanbakhsh, Maria (The Lancet Infectious Diseases, 2014)
Deworming is rightly advocated to prevent helminth-induced morbidity. Nevertheless, in affluent countries, the deliberate infection of patients with worms is being explored as a possible treatment for inflammatory diseases. Several clinical trials are currently registered, for example, to assess the safety or efficacy of Trichuris suis ova in allergies, inflammatory bowel diseases, multiple sclerosis, rheumatoid arthritis, psoriasis, and autism, and the Necator americanus larvae for allergic rhinitis, asthma, coeliac disease, and multiple sclerosis. Studies in animals provide strong evidence that helminths can not only downregulate parasite-specific immune responses, but also modulate autoimmune and allergic inflammatory responses and improve metabolic homoeostasis. This finding suggests that deworming could lead to the emergence of inflammatory and metabolic conditions in countries that are not prepared for these new epidemics. Further studies in endemic countries are needed to assess this risk and to enhance understanding of how helminths modulate inflammatory and metabolic pathways. Studies are similarly needed in non-endemic countries to move helminth-related interventions that show promise in animals, and in phase 1 and 2 studies in human beings, into the therapeutic development pipeline.